Deformation behavior of elastomeric networks studied by deuterium nuclear magnetic resonance (2H NMR) - Ekanayake, P. (Institute of Physics:Colombo, 2009)
Deuterium nuclear magnetic resonance (2H NMR) was used to test a theoretical framework that has been introduced to explain the 2H NMR line splitting of uniaxially stretched partially deuterated poly(butadiene) elastomers. The theory attributes the higher degree of anisotropy implied the splitting to the interchain steric interactions. From the fitting parameters the separate contributions to the average orientation of the chain segments arising from the network constraint and from the interactions are calculated.
Keywords: Elastomeric networks